2010
DOI: 10.1007/s10549-010-0771-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of FDG-PET in assessing axillary lymph node status in breast cancer: a systematic review and meta-analysis of the literature

Abstract: International audienceAxillary lymph node status is the most powerful prognostic indicator in patients with breast cancer. FDG-PET has been suggested as a non-invasive method of staging the axilla. The aim of this study was to review and aggregate all studies that measured the performance of FDG-PET in patients with breast cancer, using surgically obtained axillary histology as a reference, in a meta-analysis. A systematic review of the literature was performed and data extracted from all eligible studies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 38 publications
2
52
0
7
Order By: Relevance
“…the ability to detect disease, of FDG PET in breast cancer have been investigated in many studies. The consensus from several reviews is that due to its limited spatial resolution PET lacks sensitivity for the diagnostic assessment of the axilla in patients with early breast cancer [1][2][3][4][5]. Most guidelines tend to recommend PET for breast cancer only in particular circumstances (in advanced disease, for recurrences, for treatment monitoring and possibly to evaluate the efficacy of neoadjuvant therapy) [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…the ability to detect disease, of FDG PET in breast cancer have been investigated in many studies. The consensus from several reviews is that due to its limited spatial resolution PET lacks sensitivity for the diagnostic assessment of the axilla in patients with early breast cancer [1][2][3][4][5]. Most guidelines tend to recommend PET for breast cancer only in particular circumstances (in advanced disease, for recurrences, for treatment monitoring and possibly to evaluate the efficacy of neoadjuvant therapy) [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PETwi th 18 F-FDG has made important advances in the care of patients with breast cancer (1); however, 18 F-FDG PET has multiple limitations, including the inability to differentiate malignant from benign breast lesions (2), limited contribution to local staging of the breast and axillary nodes (3)(4)(5), and variable sensitivity for breast cancer depending on tumor and patient factors (6)(7)(8). Invasive lobular carcinoma (ILC), a subtype of breast cancer, is difficult to visualize by all known imaging modalities (9,10), including 18 F-FDG PET (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…On the contrary, non-radionuclide techniques such as CT and MRI have excellent spatial resolution (\1 mm). Torres Martin de Rosales et al [34][35][36] demonstrated that dual-modality imaging agents based on the conjugation of radiolabelled bisphosphonates (BP) directly to the surface of SPIO, provided excellent stability and allowed for in vivo co-localization of lymph nodes in a murine model. The application of these dual-imaging agents to future human studies provides exciting prospects to improve the sensitivity and specificity of pre-operative axillary staging.…”
Section: The Future Role Of Mnps In the Management Of The Axilla In Bmentioning
confidence: 99%